Supporting Virtual Meetings in Distributed Scrum Teams - Rodríguez, Guillermo Horacio (2012)
Scrum has gained surprising momentum as an agile project management approach. It provides effective social integration by building up social team capital, and it provides much needed control and coordination mechanisms. Especially, daily Scrum meetings ensure an open channel for communication. However, this channel has been threatened by distributed software development which has highly been adopted in software industries. To support virtual meetings regardless physical locations of team members, we developed a 3D tool based on Scrum life cycle. The tool provides a virtual world consisted in technology to hold meetings in a Scrum context. We used a questionnaire to evaluate the usability and effectiveness of the tool with undergraduate students.